# Math

How is 1/(x-2) = (2x - 6)/(x + 6) + 1 rewritten as 1/(x - 2) = 3x/(x + 6)? I don't understand.

1. 👍 0
2. 👎 0
3. 👁 44
1. 1 = (x+6)/(x+6)

so, the right hand side becomes

((2x-6)+(x+6))/(x+6)
= 3x/(x+6)

1. 👍 0
2. 👎 0
posted by Steve

## Similar Questions

1. ### Alg

Does log eqaul to baswe 10? So would logb=a be rewritten as 10^a=b? AND Why would ln5=x be rewritten as e^x=5? is it because ln also means ln(e) the e is supposed to be lowered idk how.

asked by Amy~ on June 2, 2010

Directions:Solve and explain the inequality using words.Tell which wa shading goes. Problem: x+3=>2x+1 and -4x

asked by margie on April 10, 2007
3. ### Math

1. Find the exact value of 2tan pi/12 / 1-tan^2 pi/12 root 3/3? 2. Given tanθ = -1/3 and with θ in quadrant IV, find the exact value of cos2(θ) 4/5 3. Exact value of cos^2 67.5 - sin^2 67.5 root3 /2 4. The expression cos 3θ

asked by mysterychicken on June 3, 2013
4. ### Spanish

Please check-I have to rewrite with an indirect object pronoun 1. Escribo una carta a mi abuela. Rewritten as :Le escribo una carta a mi abuela. 2.Mando una tarjeta postal a mis amigos. Rewritten as:Les mando una tarjeta postal a

asked by Ben. on November 7, 2011
5. ### Math

How is 1/(x-2) = (2x - 6)/(x + 6) + 1 rewritten as 1/(x - 2) = 3x/(x + 6)? I don't understand.

asked by Anonymous on May 8, 2014
6. ### Algebra

Could someone tell me what I am doing right or wrong? Problem Two: 5/9 + (2/9)x = 25/7 + (6/7)x – 2/3 Like signs are not collected at the beginning. This would make the equation unequal. To make both sides equal we first

asked by Aria on April 29, 2011
7. ### maths

how do i factorise this?: p^2+2p+1-t^2 thx. p^2 + 2p + 1 - t^2 = (p+1)^2 - t^2 This is the difference of two squares, so it can be rewritten =(p+1+t)(p+1-t)

asked by Emma on July 11, 2007
8. ### Math

10e^(3x-7)= 5 So what I've done is rewritten it as: (3x-7)ln10e = ln5 Now I'm a little lost as to what to do next...

asked by D.S. on April 9, 2012
9. ### Math-Calculus

Posted question rewritten lim x-> -1 108(x^2+2x)(x+1)^3 ____________________ (x^3+1)^3 (x-1)

asked by Anonymous on February 7, 2010
10. ### geometry/math

What are the components of a good definition? Can all definitions be rewritten as biconditionals?

asked by hiii on June 27, 2016

More Similar Questions